Membangun Kinerja Pegawai Melalui Kepemimpinan, Disiplin Kerja dan Motivasi Kerja: Studi Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Grobogan, Jawa Tengah - Listyaningsih, Ririn; Handayani, Rini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is to find out how leadership, discipline and work motivation impact employee performance at the Grobogan Regency Public Works and Spatial Planning Service. The population taken was a sample of seventy workers, and data was collected using a questionnaire. The research uses multiple regression analysis via the Windows SPSS 24.0 application. It is known that leadership, discipline and work motivation have a positive and significant influence on employee performance at the Grobogan Regency Public Works and Spatial Planning Service. There are also variables other than those used in this research that can explain 17.6%.